Crystallographic, Spectroscopic, and Theoretical Investigation of the Efficiently Separated 21R and 21S‐Diastereoisomers of Argatroban. Issue 12 (22nd August 2013) - Ferraboschi, Patrizia; Colombo, Diego; Legnani, Laura; Toma, Lucio; Grisenti, Paride; Vistoli, Giulio; Meneghetti, Fiorella
ABSTRACT Argatroban (I), a potent noncovalent reversible thrombin inhibitor, is used as an anticoagulant for the parenteral treatment of heparin‐induced thrombocytopenia (HIT) patients. By virtue of its pharmacological properties and the well‐balanced risks and benefits, argatroban is now emerging as a clinically relevant antithrombotic agent. The availability of this drug as a mixture of 21R and 21S‐diastereoisomers, in a ratio of roughly 64:36, prompted us to design an efficient separation setup of the two epimers. We pursued our efforts on their detailed structural analysis with the aim of understanding their different activity and aqueous solubility. These investigations were accompanied by a modeling study of the two diastereoisomers, with particular attention on the easy interconverting half‐chair of the tetrahydroquinoline system and its preferred conformation, which is determined by the configuration at C21. These results, together with the analysis of their physicochemical profiles, provide new useful information for the development of the individual diastereoisomers. Chirality 25:871–882, 2013. © 2013 Wiley Periodicals, Inc.